Implementation of the CHSE (Cleanliness, Health, Safety, Environment) Program in Tourism Health Restoration Efforts - Prihastini, Komang Angga; Jaya, Putu Prisa (GLOBAL HEALTH SCIENCE GROUP, 2024)
This prolonged pandemic period is a big obstacle for tourism managers where due to the covid-19 virus tourism, especially in Bali, is in a very worrying condition. The CHSE program created by the government is expected to be the best alternative for the restoration of Tourism Health, especially at Black Penny Villa Ubud. Objective: This research aims to find out in depth about implementation CHSE. Methods: This research uses descriptive qualitative research methods. The type of data used is primary data obtained from observations, interviews and documentation. The population used in this research was all Black Penny Villa Ubud staff, both employees and superiors. The sample chosen was 8 people was selected using purposive sampling, where those who met the inclusion criteria were willing to be respondents, as well as employees and managers who had direct contact with customers. The data that has been collected is then transcribed and then narrated into topics or subtopics. Results: Through this CHSE program, tourists can see firsthand the implementation of CHSE that has been carried out by the manager of Black Penny Villa Ubud, including the provision of evacuation routes, provision of hand washing facilities and posters related to cleanliness. Conclusion: The implementation of this CHSE program is one of the programs implemented to help tourism and creative economy business actors including hotels, travel businesses, transport businesses, tour guides, restaurants, tourist destinations, and others.